(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2019)
The study aims to analyze the techniques of controlling white rust, Pucinia horiana by using antagonistic bacteria.Â The results showed that all antagonistic microbes tested for controlling white rust (P. horiana) showed good ability to suppress because all were significantly different from the control and Pseudomonas flourescens was proven to be the most effective at suppressing the development of rust disease which was equivalent to the use of synthetic chlorotalonyl fungicides. Besides that, P. flourescens application increases plant height growth and quality of chrysanthemum flower caused by the ability of the two microbes as Plant Growth Promoting Rhizobacteria.